2000
DOI: 10.1002/(sici)1099-1581(200002)11:2<92::aid-pat941>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Modification of porous silica particles with poly(acrylic acid)

Abstract: High yields of nanocrystals at ambient temperaturehave been attained for several inorganic salts such as ZnS and CuO. The authors report one‐step, solid‐state reactions between easily obtained starting materials such as CuCl2·2H2O and NaOH to give nanoparticles with narrow size distribution. The process is carried out in air and requires no complex apparatus, reagents, or techniques and thus it shows potential for mass production of nanocrystals. All of the reactions investigated involve hydrated salts, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 8 publications
1
30
0
Order By: Relevance
“…The APS functionalized glass bead surfaces were modi ed with poly(acrylic acid) as illustrated in Scheme 2. J. T. Koch et al [14] had reported that carboxyl and amine groups react chemically with one another at 200 ± C. In our work, it was found that when the carboxyl and amine functional groups on poly(acrylic acid) and APS, respectively, were heated in DMF at 120-140 ± C amide bonds readily formed.…”
Section: Surface Modi Cation Of Glass Beads With Aps and Poly(acrylicsupporting
confidence: 52%
See 1 more Smart Citation
“…The APS functionalized glass bead surfaces were modi ed with poly(acrylic acid) as illustrated in Scheme 2. J. T. Koch et al [14] had reported that carboxyl and amine groups react chemically with one another at 200 ± C. In our work, it was found that when the carboxyl and amine functional groups on poly(acrylic acid) and APS, respectively, were heated in DMF at 120-140 ± C amide bonds readily formed.…”
Section: Surface Modi Cation Of Glass Beads With Aps and Poly(acrylicsupporting
confidence: 52%
“…After the sample was completely wetted and liquid penetration ceased the measurement was terminated. Since the method is very sensitive to the sample packing conditions, care was taken to use identical amounts of samples that were then slightly compressed in the sample holder to constant volumeas recommended [14]. The porosity of the sample was calculated from the amount of liquid that penetrated into the sample using the formula:…”
Section: Measurement Of Surface Tension Contact Angle and Porositymentioning
confidence: 99%
“…Silane coupling agents that converts hydrophilic silica into rubber‐philic are widely used in the dry rubber industry . The other reported novel techniques for modifying the surface of silica are in situ graft polymerization, admicellar polymerization and modification via macromolecular coupling agents …”
Section: Introductionmentioning
confidence: 99%
“…Lead nitrate [Pb(NO 3 ) 2 ·6H 2 O] used in adsorption experiments was purchased from Shanghai Chemical Reagents Co. China. In order to improve the metal ion adsorption capacity, silica was modified by the amination reaction using the method as described in the literature [16,17]. Fig.…”
Section: Methodsmentioning
confidence: 99%